2017
DOI: 10.1002/ajim.22750
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in asbestos cement workers in Pavia, Italy: A cohort study

Abstract: The results of this study are generally consistent with present knowledge. Conversely, our results do not support the hypothesis that pleural malignant mesothelioma risk indefinitely increases after exposure, suggesting instead that the alternative hypothesis of a risk plateau or decrease after a time since first exposure of more than 40 years is more consistent with the observed data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 9 publications
4
32
5
Order By: Relevance
“…The level of the patient’s occupational exposure to asbestos is estimated at 19.25 or 53.6 fiber·year/cc or more when calculated based on the previous literature, and the exposure level at that time is confirmed to far exceed TWA 0.1 fiber/cc, which is PEL of Occupational Safety and Health Administration (OSHA) that is currently the international standard; ELT 1.0 fiber/cc; 0.1 fiber/cm3 in the case of asbestos of 5 μm or more in length, which is REL of National Institute for Occupational Safety and Health (NIOSH); and 0.1 fiber/cc, which is TLV of Association Advancing Occupational and Environmental Health (ACGIH). Given that levels of exposure to asbestos tend to decrease over time according to previous literature [ 14 – 17 , 19 ], it is presumed that there would be a large quantity of exposure to asbestos in the 1970s when the patient worked at the factory. Considering the latent period of asbestos-related diseases is reported to be 10 to 50 years, we determined the ovarian cancer is highly correlated with the occupational exposure of asbestos and environmental exposure is a possible cause as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of the patient’s occupational exposure to asbestos is estimated at 19.25 or 53.6 fiber·year/cc or more when calculated based on the previous literature, and the exposure level at that time is confirmed to far exceed TWA 0.1 fiber/cc, which is PEL of Occupational Safety and Health Administration (OSHA) that is currently the international standard; ELT 1.0 fiber/cc; 0.1 fiber/cm3 in the case of asbestos of 5 μm or more in length, which is REL of National Institute for Occupational Safety and Health (NIOSH); and 0.1 fiber/cc, which is TLV of Association Advancing Occupational and Environmental Health (ACGIH). Given that levels of exposure to asbestos tend to decrease over time according to previous literature [ 14 – 17 , 19 ], it is presumed that there would be a large quantity of exposure to asbestos in the 1970s when the patient worked at the factory. Considering the latent period of asbestos-related diseases is reported to be 10 to 50 years, we determined the ovarian cancer is highly correlated with the occupational exposure of asbestos and environmental exposure is a possible cause as well.…”
Section: Discussionmentioning
confidence: 99%
“…Through recently published studies, it was confirmed that in a study comparing 5741 female workers exposed to asbestos until 2010, the mortality rate of ovarian cancer significantly increased (SMR = 1.38, p < 0.05) [ 13 ]. In addition, a cohort study targeted at 1818 workers at an asbestos cement factory in Italy also found that SMR of ovarian cancer was 3.64 (95% CI: 0.99–9.33) [ 14 ]. In the 2012 report, the IARC concluded in an epidemiologic study targeted at humans that asbestos has a causal relationship with laryngeal and ovarian cancer based on sufficient evidences and also has a limited correlation with colorectal, rectal, pharynx, and gastric cancer [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…As environmental exposure related to residence near asbestos-cement plants has been repeatedly reported for Casale Monferrato,15 Bari,16 Broni17 and La Spezia,18 this usage pattern may have led to sustained non-occupational exposures. The contribution of different patterns of non-occupational exposures is most likely underestimated, due to their much lower level, which, however, is not negligible and is possibly sufficient to cause disease.…”
Section: Introductionmentioning
confidence: 88%
“…The definite diagnosis of mesothelioma was made in 2012 on the basis of histological and immune-histochemical features. In particular, the patient had a sarcomatoid malignant mesothelioma at the right pleura, with a histochemical chrysotile were used to produce tubes, in a varying percent of the dry weight [18]. Thus, it is probable that the patient was exposed to both.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Moreover, despite the use of materials containing asbestos, no measurement of airborne fibers concentration is available for this factory and, probably, none was carried out before it had closed down. Furthermore, no information is available concerning the type of asbestos fiber involved in this case, however, it is likely to be a mixture of chrysotile and crocidolite, commonly used in Italy for asbestos cement products [18]. No extra-professional exposure to asbestos was identified.…”
Section: Introductionmentioning
confidence: 99%